Tujuan Pendidikan Perspektif Al-Quran dan Pendidikan Barat - Nurrohmah, Mia Roswantika; Syahid, Akhmad (CV. Creative Tugu Pena, 2020)
This article stimulated by the fact that the aim education of the Al-Qur’an perspective and western education are still not understood by various group. This condition is influenced by the lack of curiosity about the educational goals of the Al-Qur’an perspektive and westren education. The aims of article was to give a clear picture about the aim education of Al-Qur’an perspective and western education.This study revealed that the aims of education of the Al-Qur’an in relation and westren education can be known by the public. The implication of this current study is to create awareness among the society towards the educational objectives of Al-Quran and western education perspective. The method used in this study uses analytical methods, types of research, and research data sources. The data analysis method used is by using descriptive methods, namely a method that examines a condition, a system of thought or an event that occurs in the present. This type of research belong to the type of library research, namely research activities on existing data and literature. Key words: The Aims Of Education, Al-Quran, Westren Education